Assessment of a school-based intervention in eating habits and physical activity in school children: the AVall study. Issue 10 (12th March 2011) - Llargues, Esteve; Franco, Rosa; Recasens, Assumpta; Nadal, Ana; Vila, Maria; Pérez, Maria José; Manresa, Josep Maria; Recasens, Isabel; Salvador, Gemma; Serra, Jaume; Roure, Eulàlia; Castells, Conxa
Abstract : Background: Obesity has become a global public health problem, which also affects children. It has been proposed that the educational interventions during childhood could be a key strategy in the prevention of obesity. Objective: To evaluate the efficacy of an intervention on food habits and physical activity in school children. Methods: A 2-year cluster-randomised prospective study with two parallel arms was used to evaluate an intervention programme in children in their first year of primary schooling (5–6 years of age) in schools in the city of Granollers. The intervention consisted of the promotion of healthy eating habits and physical activity by means of the educational methodology Investigation, Vision, Action and Change (IVAC). At the beginning and at the end of the study (2006 and 2008) the weight and height of each child was measured in situ, while the families were given a self-report physical activity questionnaire and the Krece Plus quick test. Results: Two years after the beginning of the study, the body mass index of the children in the control group was 0.89 kg/m 2 higher than that of the intervention schools. The intervention reduced by 62% the prevalence of overweight children. Similarly, the proportion of children that ate a second piece of fruit and took part in an after-school physical activity increased in the intervention group. In the control group, the weekly consumption of fish was reduced. Conclusions: The educational intervention in healthy eating habits and physical activity in the school could contribute to lessen the current increase in child obesity.